Cross‐species sensitivity to a novel androgen receptor agonist of potential environmental concern, spironolactone. (6th September 2013) - LaLone, Carlie A.; Villeneuve, Daniel L.; Cavallin, Jenna E.; Kahl, Michael D.; Durhan, Elizabeth J.; Makynen, Elizabeth A.; Jensen, Kathleen M.; Stevens, Kyle E.; Severson, Megan N.; Blanksma, Chad A.; Flynn, Kevin M.; Hartig, Philip C.; et al.
Abstract Spironolactone is a pharmaceutical that in humans is used to treat conditions like hirsutism, various dermatologic afflictions, and female‐pattern hair loss through antagonism of the androgen receptor. Although not routinely monitored in the environment, spironolactone has been detected downstream of a pharmaceutical manufacturer, indicating a potential for exposure of aquatic species. Furthermore, spironolactone has been reported to cause masculinization of female western mosquitofish, a response indicative of androgen receptor activation. Predictive methods to identify homologous proteins to the human and western mosquitofish androgen receptor suggest that vertebrates would be more susceptible to adverse effects mediated by chemicals like spironolactone that target the androgen receptor compared with invertebrate species that lack a relevant homolog. In addition, an adverse outcome pathway previously developed for activation of the androgen receptor suggests that androgen mimics can lead to reproductive toxicity in fish. To assess this, 21‐d reproduction studies were conducted with 2 fish species, fathead minnow and Japanese medaka, and the invertebrate Daphnia magna. Spironolactone significantly reduced the fecundity of medaka and fathead minnows at 50 μg/L, whereas daphnia reproduction was not affected by concentrations as large as 500 μg/L. Phenotypic masculinization of females of both fish species was observed at 5 μg/L as evidenced by formation of tubercles in fathead minnows and papillary processes in Japanese medaka. Effects in fish occurred at concentrations below those reported in the environment. These results demonstrate how a priori knowledge of an adverse outcome pathway and the conservation of a key molecular target across vertebrates can be utilized to identify potential chemicals of concern in terms of monitoring and highlight potentially sensitive species and endpoints for testing. Environ Toxicol Chem 2013;32:2528–2541. © 2013 SETAC